Quality assurance in higher education : the Colegio De Dagupan experience - Arzadon-Sua, Feliza (Manila : National University, 2009)
This Research study entitles "Quality Assurance in Higher Education" The Colegio de Dagupan Experience was conducted in Dagupan City. It covered the operation of Colegio de Dagupan as a private higher education institution duly registered with the Securities and Exchange Commission as a non-profit, non-stock corporation.
Title page -- Approval Sheet -- Dedication -- Acknowledgement -- Table of contents -- List of tables -- List of figures -- Chapter 1. Introduction -- Chapter 2. Review of related literature and studies -- Chapter 3.Methods and Procedures -- Chapter 4. Presentation, analysis, and interpretation of data -- Chapter 5. Summary, Conclusion, and recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Design : Descriptive Method.
Includes bibliographical references.